Driving Mechanisms of an Extreme Winter Sea Ice Breakup Event in the Beaufort Sea. Issue 12 (21st June 2022) - Rheinlænder, Jonathan W.; Davy, Richard; Ólason, Einar; Rampal, Pierre; Spensberger, Clemens; Williams, Timothy D.; Korosov, Anton; Spengler, Thomas
Abstract: The thick multiyear sea ice that once covered large parts of the Arctic is increasingly being replaced by thinner and weaker first‐year ice, making it more vulnerable to breakup by winds. We use the neXtSIM sea ice model to investigate the driving mechanisms behind a large breakup event in the Beaufort Sea during winter 2013. Our simulations are the first to successfully reproduce the timing, location, and propagation of sea ice leads associated with wind‐driven breakup and highlight the importance of accuracy of the atmospheric forcing, sea ice rheology, and changes in sea ice thickness. We found that the breakup resulted in enhanced export of multiyear ice from the Beaufort Sea. Overall, this leads to a relatively thinner and weaker simulated ice cover that potentially preconditions earlier breakup in spring and accelerates sea ice loss. Finally, our simulations indicate that large breakup events could become more frequent as Arctic sea ice continues to thin. Plain Language Summary: The loss of thick multiyear sea ice in the Arctic leads to weaker sea ice that is more easily broken up by strong winds. As a consequence, extreme sea ice breakup events may become more frequent, even during the middle of winter when the sea ice cover is frozen solid. This can lead to an earlier onset of the melt season and potentially accelerate Arctic sea ice loss. Such extreme breakup events are generally not captured by climate models, potentially limiting our confidence in projections of Arctic sea ice. We investigated the driving forces behind sea ice breakup events during winter and how they change in a future climate. Our sea ice model is the first to reproduce such breakup events and reveals that the combination of strong winds and thin sea ice is a key factor for these breakups. We found that winter breakups have a large effect on local heat and moisture transfer and cause enhanced sea ice production, but also increase the overall movement of the sea ice cover, making it more vulnerable. Finally, we show that if the Arctic sea ice continues to thin, these extreme breakup events could become even more frequent. Key Points: An extreme winter breakup event in the Beaufort Sea is accurately simulated with the neXtSIM sea ice model High‐resolution and skillful atmospheric forcing, as well as appropriate sea ice rheology, are necessary to simulate such breakups In the model, thinning Beaufort Sea ice is more vulnerable to breakup, which may accelerate loss of multiyear ice